PENGGUNAAN METODE PROJECTED UNIT CREDIT DAN AGGREGATE COST PADA ASURANSI PENSIUN NORMAL - HUTABALIAN, SARAH VERONICA; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 10 No 4 (2021)DO - 10.24843/MTK.2021.v10.i04.p344, 2021)
Employees can be referred to as company assets because they play an important role in the progress and decline of a company. So the company can protect the welfare of employees when their age can no longer be productive, one of which is to include employees in pension fund insurance. This study aims to calculate and compare the normal contributions that participants must pay using the methods Projected Unit Credit and Aggregate Cost. The calculation of normal contributions using the method Projected Unit Credit uses the present value of the pension benefits divided by the length of service. The Method Aggregate Cost uses the present value of the pension benefits minus the accumulated funds and divided by the term annuity. The result of this research is that the normal contribution amount using the method Projected Unit Credit is lower in the payments in the first years than using the method Aggregate Cost. The Method contribution Projected Unit Credit increases significantly as the length of service period and the method Aggregate Cost increases slowly but increases sharply as the retirement age approaches.